Review of the Environmental Protection Agency's Draft IRIS Assessment of Formaldehyde - National Research Council (The National Academies Press, 2011)
Formaldehyde is ubiquitous in indoor and outdoor air, and everyone is exposed to formaldehyde at some concentration daily. Formaldehyde is used to produce a wide array of products, particularly building materials; it is emitted from many sources, including power plants, cars, gas and wood stoves, and cigarettes; it is a natural product in come foods; and it is naturally present in the human body as a metabolic intermediate. Much research has been conducted on the health effects of exposure to formaldehyde, including effects on the upper airway, where formaldehyde is deposited when inhaled, and effects on tissues distant from the site of initial contact. The U.S. Environmental Protection Agency (EPA) released noncancer and cancer assessments of formaldehyde for its Intergated Risk Information System (IRIS) in 1990 and 1991, respectively. The agency began reassessing formaldehyde in 1998 and released a draft IRIS assessment in June 2010. Given the complexity of the issues and the knowledge that the assessment will be used as the basis of regulatory decisions, EPA asked the National Research Council (NRC) to conduct an independent scientific review of the draft IRIS assessment. In this report, the Committee to Review EPA's Draft IRIS Assessment of Formaldehyde first addresses some general issues associated with the draft IRIS assessment. The committee next focuses on questions concerning specific aspects of the draft assessment, including derivation of the reference concentrations and the cancer unit risk estimates for formaldehyde. The committee closes with recommendations for improving the IRIS assessment of formaldehyde and provides some general comments on the IRIS development process.
Keywords: Environment and Environmental Studies; Health and Medicine

Effects of Psychoactive Chemicals on Commercial Driver Health and Performance: Stimulants, Hypnotics, Nutritional, and Other Supplements - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s Commercial Truck and Bus Safety Synthesis Program (CTBSSP) Synthesis 19: Effects of Psychoactive Chemicals on Commercial Driver Health and Performance: Stimulants, Hypnotics, Nutritional, and Other Supplements identifies available information and research gaps relating to the use of chemical substances by commercial drivers and is intended to provide up-to-date information to inform decision makers about the near-, mid-, and long-range planning needs for research and educational outreach programs.The report is designed to help the commercial transportation safety community and the Federal Motor Carrier Safety Administration in addressing issues involving the proliferation and availability of psychoactive chemical substances.Appendixes D and G to CTBSSP Synthesis 19 are available only in the pdf version of report.
Keywords: Transportation and Infrastructure

Recapturing a Future for Space Exploration: Life and Physical Sciences Research for a New Era - National Research Council (The National Academies Press, 2011)
More than four decades have passed since a human first set foot on the Moon. Great strides have been made in our understanding of what is required to support an enduring human presence in space, as evidenced by progressively more advanced orbiting human outposts, culminating in the current International Space Station (ISS). However, of the more than 500 humans who have so far ventured into space, most have gone only as far as near-Earth orbit, and none have traveled beyond the orbit of the Moon. Achieving humans' further progress into the solar system had proved far more difficult than imagined in the heady days of the Apollo missions, but the potential rewards remain substantial. During its more than 50-year history, NASA's success in human space exploration has depended on the agency's ability to effectively address a wide range of biomedical, engineering, physical science, and related obstacles—an achievement made possible by NASA's strong and productive commitments to life and physical sciences research for human space exploration, and by its use of human space exploration infrastructures for scientific discovery. The Committee for the Decadal Survey of Biological and Physical Sciences acknowledges the many achievements of NASA, which are all the more remarkable given budgetary challenges and changing directions within the agency. In the past decade, however, a consequence of those challenges has been a life and physical sciences research program that was dramatically reduced in both scale and scope, with the result that the agency is poorly positioned to take full advantage of the scientific opportunities offered by the now fully equipped and staffed ISS laboratory, or to effectively pursue the scientific research needed to support the development of advanced human exploration capabilities. Although its review has left it deeply concerned about the current state of NASA's life and physical sciences research, the Committee for the Decadal Survey on Biological and Physical Sciences in Space is nevertheless convinced that a focused science and engineering program can achieve successes that will bring the space community, the U.S. public, and policymakers to an understanding that we are ready for the next significant phase of human space exploration. The goal of this report is to lay out steps and develop a forward-looking portfolio of research that will provide the basis for recapturing the excitement and value of human spaceflight—thereby enabling the U.S. space program to deliver on new exploration initiatives that serve the nation, excite the public, and place the United States again at the forefront of space exploration for the global good.
Keywords: Space and Aeronautics

Women’s Issues in Transportation: Summary of the 4th International Conference, Volume 2: Technical Papers - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
Women’s Issues in Transportation: Summary of the 4th International Conference, Volume 2: Technical Papers includes 27 full peer-reviewed papers that were presented at the October 2009 conference. The conference highlighted the latest research on changing demographics that affect transportation planning, programming, and policy making, as well as the latest research on crash and injury prevention for different segments of the female population. Special attention was given to pregnant and elderly transportation users, efforts to better address and increase women’s personal security when using various modes of transportation, and the impacts of extreme events such as hurricanes and earthquakes on women’s mobility and that of those for whom they are responsible.TRB’s Conference Proceedings 46: Women’s Issues in Transportation, Volume 1: Conference Overview and Plenary Papers includes an overview of the October 2009 conference and six commissioned resource papers, including the two keynote presentations.
Keywords: Transportation and Infrastructure